Characteristics of minerals and oxide compounds in sediment collected from blood cockle culture areas at Bandon Bay, Thailand - YALÇINKAYA, SENAİ (My University, 2024)
Bandon Bay is a very fertile bay for coastal aquaculture, especially for blood cockles (Anadara granosa). Its structural pattern supports the flow of nutrients which directly sent from many rivers resulted the high production capacity of blood cockle at the top level in the country. Besides organic compounds present in sediment, inorganic substances are essential for growth, survival and shell development of blood cockles. A comparative study of minerals and oxide compounds which accumulated in the sediments at eight stations around the cockle culture area was conducted. These stations are located along the estuaries at Tha Thong, Tha Chang, Phum Riang, and Tapi. The proportion of oxide compounds were determinedusing X-Ray Fluorescence (XRF) technique and minerals were analyzed by Atomic Absorption Spectroscopy (AAS). Results showed that sediment characteristics, oxide composition and the amount of minerals among the stations are different from each other. The sediments of the eastern and the western coasts were characterized as crumble clay and muddy sand, respectively. Twelve types of oxide compounds, namely SiO2, Al2O3, Fe2O3, K2O, Cl, MgO, Na2O, SO2, CaO, TiO2, MnO, P2O5 were found in various quantities, with SiO2, Al2O3, and Fe2O3 were the fundamental minerals ranging from 85.64-90.82%. Tha Thong estuary in the east coast showed highly significant quantities (P<0.05) of potassium, calcium and manganese compared to the other estuaries.
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary